Real world research : a resource for users of social research methods in applied settings - Robson, Colin (Chichester, West Sussex ; Hoboken, N.J. : Wiley-Blackwell, 2011)
"Given the positive nature of the review feedback, and following the basic 'if it ain't broke ...' principle, I propose to retain the same concept of a broadly-based text with an even-handed coverage of qualitative and quantitative approaches as in previous editions. There will be a continuing focus on what I have termed 'Real World Research' and an intention for it to serve as a resource for those planning to carry out a research project.I note that there were some critical comments on the design of the text, to which you will no doubt give due consideration. The index and glossary will of course be revisited.I aim to provide a greater amount of illustrative case study material, extensively updated examples from current research to illustrate recent developments, and updated annotated further reading sections in each chapter. I will be extending the coverage of:#17;B7#18; Ethics (perhaps the adopter who provided detailed suggestions in this area could be thanked and assured that the comments will be taken on board)#17;B7#18; On-line and internet research#17;B7#18; Evidence-based approaches, including systematic reviews and meta analysis (a not uncritical discussion of this currently 'hot' topic).I will also consider the other suggestions made by adopters (some of which are, as ever, mutually contradictory). I think it unlikely that I will include student exercises as I don't really see them as appropriate for the type of book that this is. I am also dubious about including more philosophical material (including epistemology and ontology) as it can easily alienate many students. However I will have a go at this and see what I can do. There is now a substantial literature on the realist approach in practice, some of which I will cover.I will also carry out a thorough re-evaluation of the multiplicity of qualitative and quantitative approaches to see which merit inclusion. Similarly with the analysis chapters - particularly the quantitative stuff.I do not propose to make firm decisions on SPSS or NVivo at this stage. Clearly any treatment would have to be in terms of the versions current near to publication. Versions are rapidly superseded and students get twitchy if the text they are using has an older version than the one on their computer. The alternatives are in-text coverage, appendices, associated websites, or reference out. The situation is complicated for me by the fact that I am no fan of SPSS because, although very widely used, it is not ideal for the type of exploratory quantitative approach that I favour.On appendices, I will give favourable consideration to the suggestion that the material in the appendix on writing a project proposal comes within the text itself. I am very likely to retain the second appendix in its present position.I will also be giving further thought to what might go into an associated website. I am somewhat attracted to the inclusion of discipline- or area-specific examples (eg health-related, education, applied psychology, etc) on the website - rather as I have in 'How to do a Research Project'. This helps get over the problem of alienating students with text examples outside their own discipline, or of stuffing the text itself with a very large number of examples from different disciplines. As discussed earlier, I will also consider including material for lecturers such as Pow
"This bestselling text on carrying out research in 'real world' situations has been thoroughly revised and updated but continues to have the same authoritative voice and definitive content that has made it such an essential book for teachers and students conducting research within the
Keywords: Social sciences -- Resea; Methodology. 4 -- Psychology -- Resea; Methodology. 7 -- Psy